Social Isolation and Loneliness: Strong Enemies or Great Allies? (Comparative & International Education Series, 2022)
Living the experience of being an international student generates personal growth, although the process is not pleasant in all cases. When talking about being an international student, experiences such as cultural immersion, generating a global mindset, and practicing another language are highlighted. But little is said about other experiences such as isolation and loneliness during this journey.